Proceedings of the 2nd Workshop on Argumentation Mining 2015
DOI: 10.3115/v1/w15-0516
|View full text |Cite
|
Sign up to set email alerts
|

Combining Argument Mining Techniques

Abstract: In this paper, we look at three different methods of extracting the argumentative structure from a piece of natural language text. These methods cover linguistic features, changes in the topic being discussed and a supervised machine learning approach to identify the components of argumentation schemes, patterns of human reasoning which have been detailed extensively in philosophy and psychology. For each of these approaches we achieve results comparable to those previously reported, whilst at the same time ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 17 publications
1
41
0
2
Order By: Relevance
“…This could reflect that in case dirimens copulatio is indeed used to forcefully introduce a claim, the speaker anticipates this claim to be met with doubt, and therefore supports it with argumentation. 26 The high levels of support and conflict align with the idea that dirimens copulatio demands attention, and suggests that where this figure occurs, not only will it likely contribute to the argumentation structure, it will also likely be a relatively central point in the dialogue as a wholepotentially a useful characteristic for automated text summarisation [1].…”
Section: Results On Dirimens Copulatiomentioning
confidence: 99%
See 2 more Smart Citations
“…This could reflect that in case dirimens copulatio is indeed used to forcefully introduce a claim, the speaker anticipates this claim to be met with doubt, and therefore supports it with argumentation. 26 The high levels of support and conflict align with the idea that dirimens copulatio demands attention, and suggests that where this figure occurs, not only will it likely contribute to the argumentation structure, it will also likely be a relatively central point in the dialogue as a wholepotentially a useful characteristic for automated text summarisation [1].…”
Section: Results On Dirimens Copulatiomentioning
confidence: 99%
“…On the assumption that the figures can play a functional role in establishing argumentation structure, the formal dimension of rhetorical figures can be used, e.g., as a feature in machine learning approaches to argument mining. With a particular focus on concerted approaches to argument mining -in which diverse features and techniques, and insights from various disciplines and perspectives are combined to achieve the best results [26] -the first step would be to show that the forms of rhetorical figures can be identified automatically. As we have demonstrated, indeed, the very definition of various figures serves as the algorithm for their identification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Bilu et al, 2015;Kiesel et al, 2015;Nguyen and Litman, 2015;Yanase et al, 2015)) and five papers used precision, recall and F1 score (cf. (Lawrence and Reed, 2015;Sobhani et al, 2015;Park et al, 2015;Nguyen and Litman, 2015;Peldszus and Stede, 2015)) with one paper using a macro-averaged F1. What is required in the area of argument mining is a coherent model to give results for both annotator agreement but also the results of argument mining.…”
Section: Related Workmentioning
confidence: 99%
“…Previous work (Lawrence and Reed, 2015) has shown that discourse indicators such as because and therefore are very reliable predictors of argument structure. Unfortunately they are also rather rare, occurring with fewer than 10% of argumentative inference steps.…”
Section: Introductionmentioning
confidence: 99%